STRATEGI FORESIGHT UNTUK MENGUBAH PERSPEKTIF EX ANTE KE PERSPEKTIF EX POST DALAM PROSES KEPUTUSAN AUDITOR INDEPENDEN - Narsa, I Made (Jurnal Akuntansi dan Keuangan Indonesia, 2011)
This study is intended to test the effect of outcome on independent auditors’ decision, and whether the use of foresight decision aids can alter auditors’ ex-ante perspective to ex-post perspective in decision process. We use experimental design involving 206 undergraduate accounting students. They are distributed into four groups: foresight, hindsight, foresight+single outcome, and foresight-multiple outcome. We found negative outcome affects independent auditors’ decision, and foresight strategies effectively alter independent auditor’s perspective from ex-ante to ex-post perspective. We also found that in decision making process auditors consider negative information more than positive information, which reflects auditors’ conservative attitude. The results of this study can serve as a guide for auditors in improving the quality of audit planning process to prevent litigation.